Reform of the English Component in the Gaokao - Wang, Qi (International Higher Education, 2022)
As a result of an initiative of the Chinese ministry of education in 2014, an English test will be held twice a year and only the higher score will be counted in the students’ overall gaokao results. This article reviews the policy rationales of this decision and its impact on students and teachers, and discusses its implications on promoting proficiency-oriented teaching and learning and on redefining the status of English in China.